Functional Diversification of euANT/PLT Genes in Oryza sativa Panicle Architecture Determination - Luong, Ai My; Adam, Hélène; Gauron, Carole; Affortit, Pablo; Ntakirutimana, Fabrice; Khong, Ngan Giang; Le, Quang Hoa; Le, Thi Nhu; Fournel, Marie; Lebrun, Michel; Tregear, James; Jouannic, Stefan (Frontiers in Plant Science, 2021)
Grain yield, which is one of the most important traits in rice breeding, is controlled in part by panicle branching patterns. Numerous genes involved in the control of panicle architecture have been identified through mutant and QTL characterization. Previous studies suggested the importance of several AP2/ERF transcription factor-encoding genes in the control of panicle development, including the AINTEGUMENTA/PLETHORA-like (euANT/PLT) genes. The ANT gene was specifically considered to be a key regulator of shoot and floral development in Arabidopsis thaliana. However, the likely importance of paralogous euANT/PLT genes in the regulation of meristem identities and activities during panicle architecture development has not to date been fully addressed in rice. In the present study, we observed that the rice euANT/PLT genes displayed divergent temporal expression patterns during the branching stages of early panicle development, with spatial localization of expression in meristems for two of these genes. Moreover, a functional analysis of rice ANT-related genes using genome editing revealed their importance in the control of panicle architecture, through the regulation of axillary meristem establishment and meristem fate transition. Our study suggests that the paralogous euANT/PLT genes have become partially diversified in their functions, with certain opposing effects, since they arose from ancestral gene duplication events and that they act in regulating the branching of the rice panicle.